PENERAPAN LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN PERENCANAAN STUDI LANJUT PADA SISWA - Nur Khixmah Yulihastuti (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2019)
ENGLISHThis Classroom Action Research is triggered by the existence of students from Public High School 2 in Pati who did not continue their education to higher education due to social problems that became obstacles for them in planning further studies. The purpose of this study was to improve further study planning in class XII IPA, Public High School 2 in Pati in  the Academic Year conducted in two cycles, each cycle consisting of two meetings. In each cycle includes several stages:  the formation stage, the transitional stage, the activity stage and the termination stage. The results of the study showed that there was an increase for students in their advanced study planning. This can be found that  in the initial conditions  of students experiencing social problems are 10 children, it became 5 children in cycle 1 and in cycle 2 as many as 0 children. The percentage increase in advanced study planning from 74.36% to 100%. The conclusion that the effectiveness of group guidance services with successful educational alumni modeling approach is able to improve advanced study planning. INDONESIABeberapa siswa SMA Negeri 2 Pati mengalami problem sosial sehingga menghalangi mereka dalam perencanaan studi lanjut ke perguruan tinggi. Tujuan penelitian ini adalah untuk meningkatkan perencanaan studi lanjut pada kelas XII IPA 3 SMA Negeri 2 Pati tahun ajaran 2019/2020. Penelitian dilakukan dalam dua siklus, setiap siklus terdiri dari 2 pertemuan. Tiap siklus meliputi beberapa tahap, antara lain: tahap pembentukan, peralihan, kegiatan, dan tahap pengakhiran. Hasil penelitian menunjukkan peningkatan siswa dalam perencanaan studi lanjut. Hal ini dapat dilihat  pada kondisi awal siswa yang mengalami problem sosial sebanyak 10 siswa, pada siklus 1 sebanyak 5 siswa dan pada siklus 2 sebanyak 0 siswa. Persentase peningkatan perencanaan studi lanjut dari 74,36% hingga 100%. Kesimpulannya bahwa efektivitas layanan bimbingan kelompok dengan pendekatan modeling alumni sukses pendidikan mampu meningkatkan perencanaan studi lanjut.